Polycultural education as a component of the modern teacher's pedagogical work - Simonenko, Marina (Видавництво Львівської політехніки, 2011)
The content of the polycultural education and its main goal are analyzed and reflected in the article. The topicality of the modern teacher’s polycultural training as the most important condition of the youth’s polycultural education is also examined and considered in the article.
Полікультурна освіта як компонент педагогічної роботи сучасного вчителя
Keywords: multicultural education; polycultural education; multiethnic education; multinational; polycultural surroundings; teacher's polycultural training; the system of postgraduate education